Driving force for solid/liquid separation under electric field - Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2014)
The use of electric field in solid/liquid separation is especially effective with sludges containing colloidal particles for which conventional mechanical dewatering is not very successful. Such sludges are usually highly compressible, and mechanical dewatering is impeded due to very high hydrodynamic resistance of the sludges. On the other hand, the high surface charge density of colloidal particles leads to a high electroosmotic flow rate under an applied electric field. In this study, some of the factors influencing electroosmotic flow through porous materials are discussed.